Bumblebees negotiate a trade-off between nectar quality and floral biomechanics - Pattrick, J; Symington, HA; Federle, W; Glover, BJ (Cell Press, 2023)
How and why pollinators choose which flowers to visit are fundamental, multifaceted questions in pollination biology, yet most studies of floral traits measure simple relative preferences. Here, we used vertically and horizontally oriented slippery-surfaced artificial flowers to test whether bumblebees could make a trade-off between floral handling difficulty and nectar sucrose concentration. We quantified foraging energetics, thereby resolving the rationale behind the bees’ foraging decisions. The bees chose flowers with either a high handling cost or low sucrose concentration, depending on which was the energetically favorable option. Their behavior agreed with the critical currency being the rate of energy return (net energy collected per unit time), not energetic efficiency (net energy collected per unit energy spent). This suggests that bumblebees prioritize immediate carbohydrate flow to the nest rather than energy gain over the working lifespan of each bee. Trade-off paradigms like these are a powerful approach for quantifying pollinator trait preferences.